Sistem Informasi Penjualan Handmade Kerajinan Rotan Berbasis Web Menggunakan Metode Waterfall - Muqorrobin, Dawam; Astutik, Ika Ratna Indra; Azizah, Nuril Lutvi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Alfatihah shop is one of the umkm that provides various crafts made from rattan. The products they produce are various, such as chairs, sketches, wall decorations, etc. In this era of industry 5.0, the development of information technology is very rapid and fast, the competition that occurs in society is very fierce in the technological era that uses cyberspace as a sales medium. Many conventional shop sellers are starting to venture into the digital world to further increase their sales reach and with digital it makes the process of recording and organizing shop management easier. One of the media used is website media, website media has several advantages such as reaching a wider range of users, increasing company credibility and so on. To keep up with advances in information technology, the author built an Alfatihah store information system using the waterfall development method. The waterfall method is a method that is easy to use in scheduling the system development work process. The conclusion obtained from this research is that the system makes it easier for consumers to order goods using non-cash transactions, making it easier to carry out payment transactions.